How parents and families cope with chronic renal failure. Issue 7 (July 1988) - Reynolds, J M; Garralda, M E; Jameson, R A; Postlethwaite, R J
Abstract : We studied the effects on the family of childhood chronic renal failure by contrasting children with varying degrees of severity of illness with healthy controls. Disruption of family life was most common in families with the more severely ill children (on hospital haemodialysis) and there was a tendency for more mental health problems in the parents in this group. Although more of these parents reported that the child's illness had had an impact on the marriage, marital break up was not related to illness status. There were indications that illness had resulted in an increase of subjective stress but also of support in a number of psychosocial areas for parents, especially those in the more severely affected group. Nevertheless at the time of assessment, fewer mothers in this group were deriving support from their social life and fewer fathers of ill children from their jobs or finances.